Development of carbon-infiltrated biochar using oil palm empty fruit bunch as an alternative source of energy - Alya Naili binti Rozhan (Kulliyyah of Engineering, International Islamic University Malaysia, 2016)
Fossil fuels have been the main energy source worldwide, and they are facing serious depletion. Production of cokes from coals requires extensive energy and releases high amount of CO2 which leads to environmental deterioration. As one of alternatives to fossil fuels, oil palm empty fruit bunch (OPEFB) has been generated abundantly in Malaysia, but the utilization is still in a small scale due to the fact that this biomass contains more than 50% moisture, which makes it less efficient when it comes to solid biofuel production. This research presents a developed process to produce an upgraded value of OPEFB-derived biochar, namely carbon-infiltrated biochar, by integrating pyrolysis and tar decomposition processes using chemical vapor infiltration (CVI) method. In the first part of the study, OPEFB was heated slowly in an inert atmosphere to produce biochar before carbon deposition was carried out. The terminal temperature was 500°C with 10°C/min produced 78 mass% carbon content of biochar. Integrated fast pyrolysis-tar carbonization process done at 450°C with 60°C/min resulted in 5.2 mass% carbon increase. Crushing strength of these carbon-infiltrated biochar was also increased. In the second part, the biochar produced at the optimized temperature and heating rate was used as a substrate for tar decomposition to take place and for solid carbon to deposit on its pore surface. Tar source was OPEFB particles which were heated rapidly at heating rates of more than 100°C/min to produce a large amount of tar vapor containing high carbon yield. The CVI method causes tar decomposition into gases and solid carbon where the latter was loaded into porous biochar substrate to increase the carbon content and its calorific value so that it can be utilized as an alternative energy source. The product obtained was carbon-infiltrated biochar containing increased carbon content up to 6.1 mass % and consequently achieved an increased calorific value up to 26.0 MJ/kg – suitable to be used as an alternative energy source. The mechanism of carbon deposition within porous biochar was also discussed. The overall evaluation of the proposed system was carried out on the basis of its exergetic performance to confirm the advantages of the developed process system, and 41% of exergy loss was able to be achieved in comparison with the conventional system.